2019
DOI: 10.1002/ijc.32554
|View full text |Cite
|
Sign up to set email alerts
|

GPRC5A facilitates cell proliferation through cell cycle regulation and correlates with bone metastasis in prostate cancer

Abstract: The prognosis of patients with progressive prostate cancers that are hormone refractory and/or have bone metastasis is poor. Multiple therapeutic targets to improve prostate cancer patient survival have been investigated, including orphan GPCRs. In our study, we identified G Protein‐Coupled Receptor Class C Group 5 Member A (GPRC5A) as a candidate therapeutic molecule using integrative gene expression analyses of registered data sets for prostate cancer cell lines. Kaplan–Meier analysis of TCGA data sets revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 49 publications
(95 reference statements)
1
30
0
Order By: Relevance
“…In our study, increased GPRC5A expression was associated with a shorter survival. This is in agreement with results from prostate cancer, where GPRC5A expression also predicts a worse OS and was shown to be involved in metastasis since knock-down of this molecule limited bone metastasis 27 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, increased GPRC5A expression was associated with a shorter survival. This is in agreement with results from prostate cancer, where GPRC5A expression also predicts a worse OS and was shown to be involved in metastasis since knock-down of this molecule limited bone metastasis 27 .…”
Section: Discussionsupporting
confidence: 92%
“…GPRC5a is involved in epithelial cancers 27 and is proposed to be an emerging biomarker in several human cancers 28 . It was upregulated in all 3 conditions (K, L, T) ( Supplementary Fig.…”
Section: G Protein-coupled Receptor Class C Group 5 Member a (Gprc5a)mentioning
confidence: 99%
“…Among these thousands of candidates, GPRC5A was of interest in the current research because its expression had been found to be up-regulated in GC and the elevated expression of GPRC5A predicted advanced clinical features and poor prognosis [28,29]. GPRC5A was also reported to act as a potential oncogene in prostate cancer and pancreatic ductal adenocarcinoma [30,31]. Moreover, GPRC5A was involved in GC cell malignant progression through acting as a direct target of miR-204 and miR-195 [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Many observations have highlighted a strong connection between alterations in GPRC5A and several human cancers (Jiang et al, 2018), and in particular with the presence of more aggressive and metastatic phenotypes through the induction of the EMT Sawada et al, 2020;Liu et al, 2017). EMT takes place physiologically during embryonic development, tissue regeneration, organ fibrosis, and wound healing.…”
Section: Discussionmentioning
confidence: 99%